A user-friendly excel spreadsheet for dealing with spectroscopic and chromatographic data - Vieira, Alan Lima [UNESP]; Nespeca, Maurílio Gustavo [UNESP]; Pavini, Weslei Diego [UNESP]; Ferreira, Edilene Cristina [UNESP]; Gomes Neto, José Anchieta [UNESP] (Elsevier, 2019)
A user-friendly interface was developed in Excel (Microsoft Office) to deal with spectroscopic and chromatographic data. The Excel spreadsheet includes baseline correction, area and height determination, and identification of variables that represent the maximum height. In addition, the user can quickly evaluate standardization methods and create databases by adding information to the library, where up to 300 peaks can be saved. In the present work, the application of the Excel spreadsheet is exemplified by analytical curves developed with gas chromatography, Raman spectroscopy and laser-induced breakdown spectroscopy (LIBS) data. The analytical parameters obtained by the Excel spreadsheet were compared with the results generated in different software, such as MATLAB (routine), Origin and ChromQuest. The coefficient of determination (R2) and root-mean-square error (RMSE) obtained from Excel spreadsheet were very similar to those from other software. The analytical curves were also submitted to analysis of variance (ANOVA) and, regarding the F-test, all presented values of Fcalculated greater than Fcritical. The relationship between the analytical responses from the Excel spreadsheet and other software showed a coefficient of correlation close to 1. Therefore, the proposed Excel interface is an attractive alternative to expensive software and provides easy handling for LIBS data. The spreadsheet and a short tutorial video are available in the electronic supplementary material (or in the link https://1drv.ms/f/s!AjTI1LyRsk35lYtYOvj6EGyXvFgWlQ).
Keywords: Baseline correction; Chromatographic data; Excel spreadsheet; Spectroscopic data; Standardization; User-friendly interface